A Contrastive Analysis of Indonesian and English Noun Phrases: How the Differences Create Problems in Translation as Seen in “Chemistry 2A for Senior High School Grade XI Semester 1” - Anisah Durrotul Fajri (Universitas Gadjah Mada, 2012)
This research aims: 1) to find out the differences and similarities between Indonesian and English noun phrases, 2) to explain the effects of the differences and similarities between Indonesian and English noun phrases on the translation products. By using contrastive analysis Indonesian and English constructions of noun phrases are contrasted to get the differences and similarities by which the data are analyzed. The results show that Indonesian and English constructions of noun phrases have similarities and differences which create problems in translation. Those noun phrases which have differences create more problems in translation than those having similarities.